164 Racial Disparities in Surgical Recommendations for Primary Central Nervous System Tumors. (1st April 2022) - Butterfield, Jack; Golzarian, Sina; Johnson, Reid A.; Fellows, Emily; Dhawan, Sanjay; Marcotte, Erin; Venteicher, Andrew S.
Abstract : INTRODUCTION: Racial disparities in treatment and outcomes disproportionately affect patients of color in many surgical fields. There is limited research on these disparities within the field of neurosurgery and most studies report solely on outcomes, not management, of populations at a single institution. METHODS: The National Cancer Institute Surveillance, Epidemiology, and End Results database (1971-2015) was used to collect demographic and clinical variables on patients with meningioma (n = 63674), glioblastoma (n = 35258), pituitary adenoma (n = 27506), vestibular schwannoma (n = 11525), astrocytoma (n = 5402), or oligodendroglioma (n = 3977). Univariate and multivariate logistic regression were performed to identify factors independently associated with recommendation against surgical resection. RESULTS: Independent of age at diagnosis, sex, tumor histology, grade, and size, Black patients with meningioma (OR 1.20, 95% CI 1.12-1.27, p < 0.001), glioblastoma (OR 1.15, 95% CI 1.02-1.30, p = 0.023), pituitary adenoma (OR 1.19, 95% CI 1.11-1.28, p < 0.001), and vestibular schwannoma (OR 1.56, 95% CI 1.26-1.93, p < 0.001) were more likely to be recommended against surgical resection compared to White patients. Results were consistent after accounting for patient insurance status and rural-urban continuum code for the county of treatment. CONCLUSION: On review of the NCI SEER database, Black patients were more likely to be recommended against surgery compared to White patients for a number of primary CNS neoplasms, independent of clinical and demographic factors. Further research is needed to identify specific contributions to this inequity.